From the Entrepreneurial to the Ossified Economy: Evidence, Explanations and a New Perspective - Wim Naudé (Global Labor Organization (GLO), 2020)
Entrepreneurship in advanced economies is in decline. This comes as a surprise: many scholars have anticipated an upsurge in entrepreneurship, and expected an "entrepreneurial economy" to replace the post-WW2 "managed" economy. Instead of the "entrepreneurial economy" what has come into being may perhaps better be labelled the "ossified economy." This paper starts by document the decline. It then critically presents the current explanations offered in the literature. While having merit, these explanations are proximate and supply-side oriented. Given these shortcomings, this paper contributes a new perspective: it argues that negative scale effects from rising complexity, as well as long-run changes in aggregate demand due to inequality and rising energy costs, are also responsible. Implications for entrepreneurship scholarship are drawn.
Keywords: O47; O33; J24; E21; E25; 330; Entrepreneurship; start-ups; development; economic complexity; growth theory